Synodality in the Church: A Question of Yesterday and of Today - Perroni, Marinella (Asian Horizons, 2025)
The theme of synodality finds in the memory of Carlo Maria Martini’s European action as President of the CCEE (Consilium Conferentiarum Episcoporum Europae) from 1986 to 1993, that complex framework that is indispensable if we want to go beyond easy rhetoric and pursue the inculturation of faith in a culture such as the European one, to which modernity has opened up dialogue with science and democracy. The author criticizes the current ambiguous “inflation” of the term “synodality” and shows how the defeat of Martini’s project is that of a vision of the Church and a hope for Europe, and for this reason it serves as a warning: giving up the pursuit of ‘effective’ ecclesial synodality and settling for forms of ‘affective’ synodality represents the great challenge that the Catholic Church is called upon to face today. In Europe, but not only there.